Leitura compartilhada e desenvolvimento do leitor crítico no 5º ano do ensino fundamental por meio do gênero discursivo conto - Menezes, Carla Alessandra Paula da Silva (2021)
In Brazil, the results obtained in the Basic Education Assessment System (SAEB) lead researchers to point out and study about the critical state in relation to reading skills. The teaching unit, located in the municipality of Miracema – Tocantins, where the research took place in 2017, obtained an average of 3.7, not reaching the goal projected by the National Institute of Educational Studies and Research (INEP) for this year, the which should be 4.2 or higher. In addition to the statistics, we noticed that the student-reader, in reading classes, do not have a voice to speak and express themself, depending on the didactics used by the teacher. In view of this scenario, this research has the general objective of reflecting how the work with the shared reading of the short story, through theoretical and methodological orientations, can contribute to the development of reading skills in 5th grade elementary school students, enabling them responsive and critical attitudes towards the text. We considered the specific objectives: (1) to characterize shared reading activities implemented through workshops; (2) to learn how students reinterpret contents worked in the workshops, according to the skills selected for the composition of this study; (3) to characterize the effects of work with shared reading for the development of the student-reader through dialogism and responsiveness. For that, we inserted this study in Applied Linguistics, based theoretically and methodologically, in the reading strategies, defended by Solé, (1998). In addition, language is conceived as a product of interaction, according to the theoretical postulates of the Bakhtin’s Circle, considering shared reading as a social work practice. This is a qualitative and interpretative case study, carried out in a public school in Miracema-TO and has the target audience of students in the 5th year of elementary school. For the generation and collection of data, we organized the research in two stages: a diagnostic evaluation of reading and interventions in reading workshops shared with the short story genre, which is part of the literary artistic field and inserted in the study schedule in the 5th year, according to the Common National Curricular Base (BNCC, 2017). As a result, we found that the workshops with shared reading led students-readers-writers to speak, listen, participate and act critically, that is, to respond actively to teaching intervention activities. In addition, they produced a discursive reply (summary by writing) about what they managed to retain from the readings. In general, the effects of the work with shared reading revealed the students’ reflective position in relation to the texts and in dialogue with the other, represented by the classmate and the teacher-mediator.